Interaction of the DNA modifying proteins VirD1 and VirD2 of Agrobacterium tumefaciens: Analysis by subcellular localization in mammalian cells - Relić, Biserka (The National Academy of Sciences, 1998)
Interaction between Agrobacterium tumefaciens and plants provides a unique example of interkingdom gene transfer. Agrobacterium, a plant pathogen, is capable to stably transform the plant cell with a segment of its own DNA called T-DNA (transferred DNA). This process depends, among others, on the specialized bacterial virulence proteins VirD1 and VirD2 that excise the T-DNA from its adjacent sequences. Subsequent to transfer to the plant cell, the virulence protein VirD2, through its nuclear localization signal (NLS), is believed to guide the T-DNA to the nucleus. The T-DNA then is integrated into the plant genome. Although both of these proteins are essential for bacterial virulence, physical interaction of them has not been analyzed so far. We studied associations between these proteins by expressing them in mammalian cells and by testing for intracellular localization and colocalization. When expressed in human cells [HeLa, human embryo kidney (HEK) 293], the VirD2 protein homogeneously distributed over the nucleoplasm. The presence of any of two NLSs, on the N and C termini of VirD2, was sufficient for its efficient nuclear localization whereas deletion of both NLSs rendered the protein cytoplasmic. However, this double NLS mutant was translocated to the nucleus in the presence of wild-type VirD2 protein, implying VirD2–VirD2 interaction. The VirD1 protein, by itself localized in the cytoplasm, moved to the nucleus when coexpressed with the VirD2 protein, suggesting VirD1–VirD2 interaction. This interaction was confirmed by coimmunoprecipitation tests. Of interest, both proteins coimported to the nucleus showed a similar, peculiar sublocalization. The data are discussed in terms of functions of the VirD proteins. In addition, coimport of proteins into nuclei is suggested as a useful system in studying individual protein–protein interactions.